Role of the hydrophobicity on the thermodynamic and kinetic acidity of Fischer thiocarbene complexes - Andrada, Diego Marcelo (2010)
Rate constants for the reversible deprotonation of (CO)5W=C(SR)CH3 (W-SR) by OH−, water and a number of primary aliphatic and secondary alicyclic amines, have been determined in 50% MeCN: 50% water at 25 °C. In addition, solvation energy and proton affinities values for M-SR (M = Cr and W) in the gas phase and in acetonitrile have been computed at DFT level. Although there is not a linear correlation between the calculated proton affinities and the measured pKas, the calculations reveal that when solvent effects are taken into account the substituted compounds studied show differences in their proton affinities. There is a good correlation between the change in cavitation energy (ΔGcav) for the Fischer carbene complexes and log P of the thioalkyl substituents. In proton transfer reactions with amines, steric effects are more important for W complexes with respect to their Cr analogues as a consequence of differences in transition state progress. On the other hand, in reactions with OH−, hydrophobicity of the R substituent is responsible for the observed changes in intrinsic kinetic acidities, which is supported by the good correlation obtained between log k0 and log P. W complexes are more sensitive to hydrophobic effects due to the tighter solvation sphere with respect to their Cr counterparts. However, in the limit of log P = 0, the energy involved in the solvent reorganization process is the same regardless of the metal.